PERAN PEMBELAJARAN BAHASA INDONESIA DALAM PEMBENTUKAN KETERAMPILAN LITERASI DIGITAL DI ERA MEDIA SOSIAL PADA SISWA SMP NEGERI 2 BERASTAGI - Br Gurusinga, Santi Karsa (CV. Arsy Persada Quality, 2025)
The digital transformation that has hit various aspects of life has also changed the face of education, especially in terms of literacy. In the era of social media, literacy skills are no longer limited to reading and writing skills, but include the ability to understand, evaluate, and produce digital information ethically and critically. This study aims to examine the role of Indonesian language learning in shaping digital literacy skills of students at SMP Negeri 2 Berastagi. The research method used is a descriptive qualitative approach with case studies. The results of the study show that the integration of digital content and social media into Indonesian language learning significantly improves students' digital literacy, including critical thinking skills, digital communication, and ethics of interacting in cyberspace.